Entrepreneurship and Innovation in Second Tier Regions - Mayer, Heike, 1973- (Edward Elgar, 2011)
Second tier high-tech regions are taking a different path than their well-known counterparts such as Silicon Valley or Route 128 around Boston. They may lack many prerequisites of growth such as a world-class research university or high levels of venture capital funding. Often, however, they can successfully leverage anchor firms and entrepreneurial spinoffs. This book explores the evolution of these regions in the United States. The author critically examines how they evolved as knowledge-based economies, how they leveraged entrepreneurship and innovation, and ultimately how they employed public policy to support economic growth. Filling a gap in the literature, the book speaks to researchers and policymakers across the fields of entrepreneurship, economic geography and economic development planning. Entrepreneurship researchers will find this book interesting because it focuses on the role of new venture creation in regional economic development.